Analisis Keterampilan Kolaboratif Murid dalam Pembelajaran Biologi - Bunga Fadelia; Relsas Yogica; Lufri Lufri; Zulyusri Zulyusri (Al-Alam: Islamic Science Education Journal, 2026)
This study aims to analyze the collaborative skills of students at Payakumbuh State High School 3 in their biology classes. This study employs a quantitative descriptive approach using a questionnaire administered to 72 students in grades XI F6 and XI F7. Data were collected through a closed-ended questionnaire containing 13 questions measuring aspects of learning interest, study habits, use of learning resources, group participation, self-confidence, responsibility, and difficulties in collaborating. The results indicate that 100% of students are interested in Biology learning, yet only 45.8% feel confident expressing their opinions in front of peers. A total of 90.3% of students have experienced difficulties in group work, with the main issues being the presence of passive members (73.6%) and a lack of cohesion (52.7%). Although 100% of students are accustomed to valuing their peers’ opinions and acknowledge the importance of social skills (95.8%), the majority (62.5%) are more comfortable learning independently than in groups. These findings indicate that students’ collaborative skills still need to be improved through more varied and structured learning strategies.